Transformasi Pembayaran Internasional: Peran CBDC dan Integrasi dengan Ekosistem Fintech - Nurul Setiyaningsih; Nurul Aina Romadhoni; Pranashinta Intan Berlianna; Regitasari Setyaning Uttami; Pungky Lela Saputri (CEMERLANG : Jurnal Manajemen dan Ekonomi Bisnis, 2025)
This article discusses the transformation of international payments that continues to develop along with technological advances and increasing needs for efficiency, speed, and security in conducting cross-border transactions. This development is marked by the innovation of international payments with the existence of CBDC (Central Bank Digital Currency) and its integration with fintech, as a digital currency issued by the Central Bank. In this study, the research method used is a qualitative descriptive method. Where data can be obtained through informal group discussions, literature studies, and from various sources of information related to the transformation of international payments, CBDC, and the fintech ecosystem. The results of the study show that there has been a transformation of international payments that started from manual or cash transactions, until now it can carry out digital payment transactions using CBDC payment innovations. However, there are challenges or risks in using CBDC, namely related to data security and privacy, new financial technology regulations, changes in consumer behavior, and financial stability risks. This article is expected to provide insight for industry players to be able to utilize the potential of CBDC and fintech in building a more modern and sustainable international financial system.